Monthly cyclicality in retail Investors’ liquidity and lottery-type stocks at the turn of the month - Meng, Yun; Pantzalis, Christos (Journal of Banking & Finance, 2018)
The well-documented underperformance of lottery stocks masks a within-month cyclical pattern. Demand for lottery stocks increases at the turn of the month, especially in areas whose demographic profile resembles that of typical lottery-ticket buyers (i.e., gamblers), thus driving their prices higher. This effect is rooted in local retail investors’ preference for lottery stocks and propelled by the within-month cyclicality of local investors’ personal liquidity positions. A long-short investment strategy based on this cyclical pattern of lottery stocks’ performance yields gross abnormal returns of about 12.6% per year.